The common causes of rework in construction contracts: a diagnostic approach - Asadi R; Wilkinson S; Rotimi JOB (Emerald, 2021)
Purpose: The high rate of rework that occurs in construction projects has a negative effect on the performance of the construction projects. Although several mechanisms have been implemented to control reworking, a comprehensive list of rework causes is yet to be provided to present the common causes that contribute to rework in construction contracts. This paper aims to investigate the most common rework causes that need to be addressed in construction contracts. Design/methodology/approach: A mixed-method using both the qualitative and quantitative approach is used in this paper. First of all, the study adopted a four-step literature review to introduce the rework research trends and provide statistical reports using descriptive analysis. Next, a comprehensive review has been completed using content analysis to identify the common causes of rework in construction projects. Finally, the common causes in construction contracts are further investigated through a quantitative questionnaire survey to validate the initial results. Findings: The results of the review showed an increasing trend of publications on rework over the last three decades. Most of the studies were conducted in Australia, the UK, Nigeria and Hong Kong. Based on further investigation in the study area of sources of rework, 37 causes of rework causes were identified and classified in five groups. Then, the most significant causes of rework in construction contracts were compiled in the list of 22 items. Research limitations/implications: The paper’s reported result, contributes to the contract management body of knowledge by proposing a list of common rework causes that can be used by practitioners during the contract negotiation to prevent contractual issues. The result of the review can also be used for further investigation of the relationship between rework and contract conditions. Originality/value: The proposed list of common causes of rework in construction contracts allows project parties to improve the terms of the contract in addressing rework, this could result in fewer contractual claims and disputes. The findings of this study will also guide the investigations into the contract conditions, thus the approach used is constructive.
Keywords: 09 Engineering; 12 Built Environment and Design